23rd International Conference on Offshore Mechanics and Arctic Engineering, Volume 1, Parts a and B 2004
DOI: 10.1115/omae2004-51506
|View full text |Cite
|
Sign up to set email alerts
|

Wave Amplification and Possible Deck Impact on Gravity Based Structure in 10-4 Probability Extreme Crest Heights

Abstract: Model tests with a Gravity-Based Structure (GBS) platform in extreme waves are presented. First, the background for the experiments is given, based on the analysis of a possible late life production scenario in the Statfjord field. The statistical approach applied in the specification of the wave conditions, and the laboratory reproduction is then described. This is focused on the generation of a statistical ensemble of 50 extreme crests sampled from random wave realisations. The model test set-up and instrume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 0 publications
2
12
2
Order By: Relevance
“…Whilst the present results specifically relate to wid loads, they are consistent with earlier studies (Kjeldsen and Myrhaug, 1979;Chaplin et al, 1992;Stansberg et al, 2012;Stansby et al, 2013) that have demonstrated the importance of wave breaking in respect of the fluid loads acting on either a flat plate or a fixed vertical column. However, when compared to the wid loads reported by Stansberg et al (2004), the present records exhibit a more gradual reduction in the applied load following the maximum. This is a direct consequence of the difference in the porosity of the topside structure; the earlier work by Stansberg et al (2004) involving a fully-plated structure.…”
Section: Type Of Wave Breakingcontrasting
confidence: 63%
See 1 more Smart Citation
“…Whilst the present results specifically relate to wid loads, they are consistent with earlier studies (Kjeldsen and Myrhaug, 1979;Chaplin et al, 1992;Stansberg et al, 2012;Stansby et al, 2013) that have demonstrated the importance of wave breaking in respect of the fluid loads acting on either a flat plate or a fixed vertical column. However, when compared to the wid loads reported by Stansberg et al (2004), the present records exhibit a more gradual reduction in the applied load following the maximum. This is a direct consequence of the difference in the porosity of the topside structure; the earlier work by Stansberg et al (2004) involving a fully-plated structure.…”
Section: Type Of Wave Breakingcontrasting
confidence: 63%
“…However, when compared to the wid loads reported by Stansberg et al (2004), the present records exhibit a more gradual reduction in the applied load following the maximum. This is a direct consequence of the difference in the porosity of the topside structure; the earlier work by Stansberg et al (2004) involving a fully-plated structure. A detailed investigation of the role of topside porosity is presently on-going.…”
Section: Type Of Wave Breakingcontrasting
confidence: 63%
“…First, there has been a number of studies considering multiplecolumn structures. These include the studies of Swan et al [1], Ohl et al [2,3], Stansberg et al [4], Stansberg & Kristiansen [5] and Walker et al [6]. In all cases, these indicate significant departures from the classical diffraction solutions.…”
Section: Introductionmentioning
confidence: 92%
“…bases are regarded. The gravity platform is not attached to the soil [1] and wave-induced force is obtained using Erie linear wave theory [2], [4], [5] for a regular wave. Since the geographical location of platforms is located in the North Sea according Figure (1), the environmental conditions and specifications of Concept definition and project organization are as follows: Geometry & Environmental modeling Property:…”
Section: Methodsmentioning
confidence: 99%